Նշխարներ Նոր Նախիջևանի հայ ժողովրդական բանահյուսությունից (Նոր Նախիջևանի հիմնադրման 240-ամյակի առթիվ) - Վերժինե Սվազլյան (ՀՀ ԳԱԱ հրատ.)
Армяне-переселенцы из Крыма адаптировались в новой, русской среде, которая стала для них родной. Свидетельством тому являются сложенные ими народные произведения, действия героев которых сопряжены не только с Ростовом-на-Дону и окрестными армянскими селами, но и с русскими городами Новочеркасском и Таганрогом. The Armenian settlers from Crimea, adapted to the new, Russian environment, which became a homeland for them. The evidence for that are observed in the popular creations they have narrated, where the actions of the heroes are not only from Rostov and the neighboring Armenian villages, but also from the Russian towns of Novocherkask and Taganrog.
Keywords: Philology; Linguistics; Language and Literature; G Geography; Anthropology; Recreation; GR Folklore